APROPRIAÇÕES DA FILOSOFIA MONTESSORIANA PARA O ENSINO DE MATEMÁTICA NOS CADERNOS DO COLÉGIO MARIA MONTESSORI DE CAMPO GRANDE MS (1980-1999) - Angela Regina da Silva (2023)
The objective of this dissertation is to characterize, in historical perspective, the appropriations of the founders of the Maria Montessori College of Campo Grande, Mato Grosso do Sul, performed the Montessori philosophy for the teaching of mathematics. The research had as guiding question: what appropriations were made of Montessori philosophy in order to constitute representations in the training of teachers who taught Mathematics at the Maria Montessori College of Campo Grande, Mato Grosso do Sul? In order to answer this question, we analyzed personal files of the founders Eliza Augusta Castilho Dias Pinho and Maria Sheila Oliveira Saldanha dating from 1980 to 1999. Among the personal files, there are two notebooks that we took for analysis and called them reference notebooks. For the analysis, we rely on references from cultural history, such as Certeau (1982), Julia (2001), Chartier (1990, 1991), Bloch (2005), Burke (1992). We also conducted an interview with the founders and the pedagogical coordinator, in which we learned of a teacher who taught all subjects, including Mathematics, for more than 35 years at the school. This information led us to the sources analyzed in the research. During the investigation, systematization and inventory of sources, we found a movement of appropriation by different means: courses, handouts and lectures, in addition to the works of Maria Montessori and the presence of institutions/organizations that convey the Montessori philosophy in Brazilian soil. Still, in this movement, we found that the founders made trips to study the Montessori system of teaching, which we consider as pedagogical trips (Mignot; Gondra, 2007). In the analysis of the reference notebooks, we identified guidelines for the teaching of the Great vision of numeration, composition and fundamental operations: addition, subtraction, multiplication and division, in the use of Montessori materials. In the guidelines, new uses and meanings were attributed to Montessori materials, such as the inclusion of material resources such as the roll for recapitulation and the elaboration of games aimed at teaching mathematics. In addition, the guidelines for training teachers bring representations of the Three-Time Lesson in Montessori (1965) for teaching mathematics. We found that this perspective permeates the teaching of mathematics through guidelines for training teachers and in the understanding of child development, based on principles of self-education, freedom and autonomy, since the notes brought, in concomitance, the teaching of mathematics, the Montessori philosophy and its elements. Therefore, we consider that Eliza Augusta and Maria Sheila made appropriations of the Montessori philosophy for the teaching of mathematics which generated representations for the training of teachers at the Maria Montessori College of Mato Grosso do Sul. Keywords: Maria Montessori, Appropriations, History of mathematics education, professional knowledge; Mato Grosso do Sul; Personal archives.